Intranasal Immunization of Mice with Influenza Vaccine in Combination with the Adjuvant LT-R72 Induces Potent Mucosal and Serum Immunity Which Is Stronger than That with Traditional Intramuscular Immunization - Barackman, J. D. (American Society for Microbiology, 1999)
Immunization of mice by the intranasal route with influenza virus hemagglutinin in combination with the mutant Escherichia coli heat-labile enterotoxin R72 (LT-R72) induced significantly enhanced serum and mucosal antibodies, surpassing, in most cases, responses achieved by traditional intramuscular immunization using inactivated split influenza vaccine. Furthermore, intranasal immunization with LT-R72 induced a potent serum immunoglobulin G2a response, indicating that this adjuvant has Th1 character.